Microbial susceptibility profile trend of blood culture isolates in a third level hospital - Cayo Castillo, Jose Johao (2022)
Objective: To describe the trend of antibiotic sensitivity in microorganisms isolated in blood cultures in patients of a tertiary care hospital. Material and methods: Observational-descriptive study corresponding to the period 2011-2017 at Hospital III Daniel Alcides Carrión. The identification and antimicrobial sensitivity of the blood culture isolates were determined using the automated Vitek® system. Results: 1056 positive blood cultures were found. Gram-negatives were obtained in 38.4 %, Gram-positives in 59 %, and yeasts in 2.6 % of the samples. The most frequent isolated pathogen was coagulase-negative Staphylococcus, with 39.7 %. The service that presented the highest number of blood cultures with positive results was the non-ICU hospitalization unit. The antimicrobials that showed greater sensitivity were ertapenem (100 %) in E. coli, vancomycin (100 %) in coagulase-negative Staphylococcus, and vancomycin (99 %) in Staphylococcus aureus. Conclusions: The pathogen with the highest frequency is coagulase-negative staphylococci, while the department with the highest number of positive results is non-ICU hospitalization. Studies of resistance phenotypes of these microorganisms that are under epidemiological surveillance are recommended.